2016
DOI: 10.1088/0960-1317/26/5/055011
|View full text |Cite
|
Sign up to set email alerts
|

A low cost, disposable cable-shaped Al–air battery for portable biosensors

Abstract: A disposable cable-shaped flexible battery is presented using a simple, low cost manufacturing process. The working principle of an aluminum–air galvanic cell is used for the cable-shaped battery to power portable and point-of-care medical devices. The battery is catalyzed with a carbon nanotube (CNT)-paper matrix. A scalable manufacturing process using a lathe is developed to wrap a paper layer and a CNT-paper matrix on an aluminum wire. The matrix is then wrapped with a silver-plated copper wire to form the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…A submerging test was carried out and it was found that the cable‐type lithium–air battery could effectively power a commercial LED in water. Inspired by this design, a cable‐type aluminum–air battery was also proposed in recent studies . Compared with the sandwich structure, the cable‐type design possesses high tensile strength in the twisted state and has extreme omnidirectional flexibility, which ensures their potential use in flexible electronic devices.…”
Section: Prototype Flexible Metal–air Batteriesmentioning
confidence: 99%
“…A submerging test was carried out and it was found that the cable‐type lithium–air battery could effectively power a commercial LED in water. Inspired by this design, a cable‐type aluminum–air battery was also proposed in recent studies . Compared with the sandwich structure, the cable‐type design possesses high tensile strength in the twisted state and has extreme omnidirectional flexibility, which ensures their potential use in flexible electronic devices.…”
Section: Prototype Flexible Metal–air Batteriesmentioning
confidence: 99%
“…Xu et al developed a fiber‐shaped AAB based on a silver nanoparticle‐coated CNT air cathode and a spring‐like Al anode, which achieved a high specific capacity of 935 mAh g −1 and a high energy density of 1168 Wh kg −1 at 0.5 mA cm −2 . In addition, Fotouhi et al designed a low cost, disposable fiber‐shaped AAB for portable point‐of‐care diagnostic devices, which could be on‐demand activated by absorbing buffer solutions (PBS) and alkaline solutions, with a power of over 1.5 mW. Because thermodynamically, aluminum cannot be electrodeposited in aqueous electrolytes, these Al‐air batteries are not rechargeable, which has seriously limited their practical applications.…”
Section: Summary Of Fiber‐shaped Batteriesmentioning
confidence: 99%
“…Those carbon materials have some unique functions in metal–air batteries because of their special structures and numerous defects. Those carbon materials mainly include carbon nanotubes (CNTs), carbon nanofibers (CNFs), graphene, graphite, and carbon microfibers. , Graphene has been applied as metal-free catalysts or catalyst support in fuel cells. It has advantages of large surface area, high conductivity, and thermal and chemical stability. Therefore, the graphene is used to fabricate electrodes for metal–air batteries.…”
Section: Air Cathode Materialsmentioning
confidence: 99%